Effectiveness of Visual Communication of Smoking Ban on Cigarette Packaging in Thailand and Indonesia on the Decline of Smoking Prelevance : Krong Thip and Sampoerna Case Study - Hadi Baku Pangestu; Ferry Darmawan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Indonesia and Thailand, both Southeast Asian countries with high levels of cigarette consumption, have implemented health warning images on cigarette packs as a strategy to reduce smoking prevalence. This study aims to analyze and compare the effectiveness of these warning images in creating a deterrent and fear effect on smokers in both countries. Using Roland Barthes' semiotic method, this study focuses on visual elements such as image, size, and text message. The findings show that in Indonesia, images of lung cancer victims with scary textual warnings are pasted on the packaging, whereas in Thailand, the images used are more varied and larger in size, creating a stronger visual impact. Data from the Indonesian Ministry of Health and Thailand's Global Action to End Smoking revealed that there will be 70 million smokers in Indonesia by 2024 and 11.5 million in Thailand by 2022. The comparative results suggest that the larger and more varied health warnings in Thailand may be more effective in attracting attention and triggering emotional responses compared to the more homogenous approach in Indonesia. In conclusion, the results of this study suggest that effective visual warnings can influence smokers' awareness and behavior, providing important insights for the development of more dynamic public health policies tailored to each country's cultural context in tobacco control efforts.